Parâmetros cardiopulmonares e metabólicos nas transições de intensidade do teste cardiopulmonar de exercício em homens treinados na resistência aeróbia e de força muscular - Rodrigues, Jhennyfer Aline Lima (2014)
Physical exercise is an important external challenge to the homeostasis of the cellular environment. Cardiopulmonary and metabolic parameters differ in response to graded aerobic exercise endurance and muscular strength. A particularly striking phenomenon in the metabolic response to progressive exercise is the occurrence of a change in the relationship between the increase rates on the production o carbon dioxide (VCO2) and the uptake of oxygen (VO2). This break in the linearity, identified as ventilatory anaerobic threshold (VAT), corresponds to the transition of aerobic to anaerobic metabolism and it is also an index that reflects physical fitness in a satisfactory way. The time between the VAT and respiratory compensation point (RCP), associated with a stabilization of end tidal carbon dioxide (PetCO2) is termed as phase II of cardiopulmonary exercise testing (CPET) and corresponds to isocapnic buffering (IT). Considering the different cardiometabolic adaptations resulting from resistance aerobic training and muscular strength, this work aimed to study the cardiovascular and ventilatory responses during phase II of CPET in trained individuals in aerobic endurance and muscular strength. 91 healthy men intentionally distributed in three groups were elected: control (CON n = 38), intense resistance exercise (IRE n = 23) and endurance runners (ER n = 30). The three groups performed CPET. The subjects' age ranged from 21 to 55 years old. The ER showed higher VO2VAT; VO2RCP and VO2máx (36±8 ml.kg-1.min-1; 46±8 ml.kg-1.min-1; 51±8 ml.kg-1.min-1 vs 24±6 ml.kg-1.min-1; 35±5 ml.kg-1.min-1; 40±6 ml.kg-1.min-1 e 26±6 ml.kg-1.min-1; 35±6 ml.kg-1.min-1; 40±7 ml.kg-1.min-1.P<0,05), compared to CON and IRE respectively, even after allometric correction. HRREP was significantly lower in the ER vs CON (CE= 52±6 bpm; CON= 60±8 bpm; P<0,05). Trained differ regarding control for HRRCP and HRPEAK (ER= 165±14 bpm; 179±11 bpm; IRE= 163±18 bpm; 181±8 bpm vs CON= 174±14 bpm; 190±10 bpm. P<0,05). The VEVAT and VERCP was higher in ER (62±14; 93±17) vs CON (45±14; 74±18), no differences for IRE (54±12; 82±15) P<0,05. The ER and IRE showed higher VCO2VAT (2,39±0,56 e 2,09±0,49), respectively compared to CON (1,64±0,51) P<0,05. In RCP VCO2 showed differences only for the ER vs CON (3,45±0,54 vs 2,82±0,64) respectively, P<0,05. The RTRRCP was lower in IRE (1,03±0,05) vs ER (1,12±0,20) and CON (1,09±0,08) P<0,05. In phase metabolic transition, significant differences in relation to the ER, CON and IRE, for the load (km / h): 4,2±1,6 vs 2,7±1,6 e 2,8±1,0, respectively P<0,05. The oxygen pulse was also lower in endurance runners (ER= -0,0474; CON= 0,0222 e IRE= 0,0275. P<0,05). The ECINCLINA was lower for the ER 80 and 90% of CPET CON compared to CPET and 100% compared to the IRE. It was concluded that the ER has greater magnitude of difference in the transition load compared to CON and IRE at a uptake of oxygen similar between groups; Between IRE and CON there were no differences in cardiopulmonary parameters evaluated in this study, except for HRRCP and RTRRCP; There is evidence from greater metabolic efficiency ER and, consequently, reduced muscle fatigue compared to CON and IRE.